Maximizing Rail Performance: How Material Requirements Planning Optimization Shapes the Future of Operational Efficiency at PT KAI, Bandung - Adhie Fasha Nurhadian; Galih Putra Prawiranegara; Irena Larashati; Windi Matsuko Danasasmita; Indri Ayu Tansar; Asep Rochyadi Suherman; Ashila Dwiyanisa; Muhammad Nuin Hayat Pajar; Ghina Ananda Rhamadanty Yanuar Priadi; Patwa Wandiandi; Fitri Putri Sobari; Amelia Shaky Andara (LPPM STMIK Mardira Indonesia, 2025)
This paper addresses the operational challenges at PT KAI, Bandung, where fragmented material tracking and inefficient inventory scheduling frequently lead to maintenance delays and inflated holding costs for critical railway spare parts. To resolve these issues, this joint research and community service project aims to optimize the Material Requirements Planning (MRP) system, thereby accelerating operational efficiency and safeguarding schedule punctuality. We adopted a qualitative research design, deploying a collaborative team of university lecturers and students to conduct in-depth interviews, field observations, and document analyses. We analyzed the qualitative data using thematic analysis and process mapping to evaluate how the optimized MRP framework impacts daily maintenance workflows. The results demonstrate that optimizing the MRP system drastically eliminates redundant inventory, shortens lead times for critical maintenance components, and significantly reduces operational waste. By establishing an integrated, data-driven scheduling workflow, PT KAI successfully minimized maintenance downtime and stabilized its supply chain.